Surface structure influences contact killing of bacteria by copper. Issue 3 (17th April 2014) - Zeiger, Marco; Solioz, Marc; Edongué, Hervais; Arzt, Eduard; Schneider, Andreas S.
Abstract Copper kills bacteria rapidly by a mechanism that is not yet fully resolved. The antibacterial property of copper has raised interest in its use in hospitals, in place of plastic or stainless steel. On the latter surfaces, bacteria can survive for days or even weeks. Copper surfaces could thus provide a powerful accessory measure to curb nosocomial infections. We here investigated the effect of the copper surface structure on the efficiency of contact killing of Escherichia coli, an aspect which so far has received very little attention. It was shown that electroplated copper surfaces killed bacteria more rapidly than either polished copper or native rolled copper. The release of ionic copper was also more rapid from electroplated copper compared to the other materials. Scanning electron microscopy revealed that the bacteria nudged into the grooves between the copper grains of deposited copper. The findings suggest that, in terms of contact killing, more efficient copper surfaces can be engineered.